EU-UKRAINE RELATIONS DEVELOPMENT POLICY: HISTORICAL BACKGROUND AND CURRENT STATE - Holovko, Svitlana; Vodolaskova, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the study is a scientific and historical analysis of international relations, legal characteristics, structure and features of the main legal documents that form the basis of Ukraine-EU relations. Research methods: the methodological basis of the work is a comprehensive approach to the analysis of the conceptual foundations of Ukraine-EU relations. It is based on the dialectical method of research, as well as the method of historicism, analytics and comparisons, which provide identification of internal nature to predict further developments in the dialectical and historical dimension for applied use, namely: implementation of modern Ukrainian legislation to European Union standards. Results: the relevance of historical and legal analysis and research of legal documents that form the basis for relations between Ukraine and the European Union at certain historical stages, follows from the need to create a theoretical basis for the development of further Ukraine-EU relations. With the conclusion of the Agreement, relations between Ukraine and the EU will be taken to a new level - from partnership and cooperation to political association and economic integration. An important element of the Agreement is to ensure a deep and comprehensive free trade area. Ukraine views the Association Agreement as an important step towards the next stage - preparation for EU accession. Discussion: in addition to scientific value, as well as opportunities for application in the educational process of this article, it is relevant to the legislative process. Because the practical significance of the article is that it provides an opportunity to focus legal doctrine on the needs of practice, namely, in order to bring Ukrainian legislation into line with the main regulatory norms of the European Union.